A Dual‐Ion Organic Symmetric Battery Constructed from Phenazine‐Based Artificial Bipolar Molecules. (29th April 2019) - Dai, Gaole; He, Yan; Niu, Zhihui; He, Ping; Zhang, Changkun; Zhao, Yu; Zhang, Xiaohong; Zhou, Haoshen
Abstract: Symmetric batteries received an increasing research interest in the past few years because of their simplified fabrication process and reduced manufacturing cost. In this study, we propose the first dual‐ion organic symmetric cell based on a molecular anion of 4, 4′‐(phenazine‐5, 10‐diyl)dibenzoate. The alkali salt of 4, 4′‐(phenazine‐5, 10‐diyl)dibenzoate allows a facile transport of cations and large anions, and remains stable in both oxidized and reduced states. The large potential difference between phenazine and benzoate results in a high cell voltage of 2.5 V and an energy density of 127 Wh kg −1 at a current rate of 1 C. The introduction of bipolar organic materials may further consolidate the development of symmetric batteries that are fabricated from abundant elements and environmentally friendly materials. Abstract : Geladene Aromaten : Das 4, 4′‐(Phenazin‐5, 10‐diyl)dibenzoat‐Anion wird in der Konstruktion einer organischen symmetrischen Doppelionenbatterie verwendet. Die gute Leistung dieser Batterie belegt, dass durch die Einführung dieses organischen Moleküls die Einschränkungen in der Spannung und Energiedichte, die Anorganik‐basierte symmetrische Batterien mit sich bringen, überwunden werden können.